The Interpersonal Communication of Hijrah Laundry Coin Public Relations is an Effective Method for Maintaining Customer Loyalty in Medan, Johor - Mhd Rifqi Aulia (Indonesian Journal of Communication and Social, 2024)
The rapid development of science and technology has undoubtedly spurred the emergence of many businesses, both in the service and manufacturing sectors. The laundry service industry is currently one of the fastest-growing businesses, in line with the increasing population growth. The coin laundry business is fiercely competitive. To win the race, businesses must excel in price, quality, excellence and knowledge development. The right marketing and communication strategy is essential for success. Hijrah Laundry Coin is one of the leading laundry coin businesses in Medan, Johor. Since opening its doors in February 2020, Hijrah Laundry Coin has been a dominant force in the coin laundry business, operating from Jalan Karya Wisata Ujung No. 23, gedung Johor, Medan Johor District, North Sumatra. Hijrah Laundry Coin can serve 35-50 customers a day with clothes dry cleaning services. Given its relatively short existence, Hijrah Laundry Coin has succeeded in gaining customer loyalty. This study aims to identify the interpersonal communication strategies employed by public relations, specifically the owner and employees of Hijrah Laundry Coin, to gain customer trust and establish customer loyalty. This research employs a descriptive qualitative methodology. Data are collected through observation, interviews, and documentation. In the context of intense competition for customer loyalty in Medan Johor, informant Anis has chosen to build a friendship relationship with her customers. Such a relationship can create internal and emotional bonds that persuade customers to remain loyal to Hijrah Laundry Coin.